Your Mouth is the Mirror of Health and Disease of the Gastrointestinal System: Oral Mucosal Manifestations of Gastrointestinal Disease - Dingley, Anya (Trinity Student Medical Journal, 2025)
Introduction: Over the last few years, the importance placed on multi-disciplinary approach to patient care has been increasing. One such relationship is the between a dentist and medical practioner. Methods: This narrative review examines the manifestations of gastrointestinal diseases in the oral mucosa. Understanding the interconnection between the oral cavity and gastrointestinal conditions can help with early diagnosis and can serve as an indicator of disease progression. The aim of this narrative review is to underscore the importance of recognising these suspicious oral mucosal signs and understand the bi-directional relationship between oral health and systemic well-being. Results: The findings highlight the need to integrate oral examinations in patients at high risk of or with suspected or current gastrointestinal diseases. A holistic approach will help in better patient care and overall patient outcomes. Discussion: There exists a gap in diagnostic approaches for oral manifestations of gastrointestinal diseases, which must be bridged to efficiently facilitate early diagnosis and treatment of these diseases. Understanding this inter-play between oral health and systemic well-being will significantly improve patie